La falta de motivación del laudo arbitral afecta su validez, provocando nulidad - Hidalgo Fernández, José Luis (2019)
In Ecuador, arbitration as an alternative method of conflict resolution has become a system widely used by citizens to solve legal problems due to their own characteristics. The Arbitration Tribunal issues an arbitration award containing the decision taken on the specific case. According to the Law on Arbitration and Mediation, the only mechanism for challenging the arbitration award is the nullity action contemplated in article 31 of the aforementioned regulatory body, which contains five grounds for which the action could be exercised. It has been argued for a long time that the grounds of article 31 of the Law on Arbitration and Mediation are “taxative” and that, exercising the nullity action based on a cause not provided for in article 31 is not legally possible, which at the discretion of the undersigned would obviously cause violation of constitutional rights by not being able to challenge the award for a cause other than those provided by law…….